2016
DOI: 10.1002/cne.24065
|View full text |Cite
|
Sign up to set email alerts
|

Impaired constitutive and regenerative neurogenesis in adult hyperglycemic zebrafish

Abstract: A growing body of evidence supports hyperglycemia as a putative contributor to several brain dysfunctions observed in diabetes patients, such as impaired memory capacity, neural plasticity, and neurogenic processes. Thanks to the persistence of radial glial cells acting as neural stem cells, the brain of the adult zebrafish constitutes a relevant model to investigate constitutive and injury-induced neurogenesis in adult vertebrates. However, there is limited understanding of the impact of hyperglycemia on brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 89 publications
4
54
1
Order By: Relevance
“…PCNA, S100β, and GFAP antibodies have been previously documented for their use and their specificity in mouse and in zebrafish according to manufacturer's instruction and/or literature (Diotel et al, ; Diotel, Beil, et al, ; Dorsemans, Soule, et al, ; Marz et al, ). Consistent with these previous studies, PCNA‐labeling was observed in cell nuclei across the neurogenic niches lining the ventricles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCNA, S100β, and GFAP antibodies have been previously documented for their use and their specificity in mouse and in zebrafish according to manufacturer's instruction and/or literature (Diotel et al, ; Diotel, Beil, et al, ; Dorsemans, Soule, et al, ; Marz et al, ). Consistent with these previous studies, PCNA‐labeling was observed in cell nuclei across the neurogenic niches lining the ventricles.…”
Section: Methodsmentioning
confidence: 99%
“…For mouse, immunohistochemistry was performed on 12 μm thickness transverse cryostat sections. Briefly, the brain sections were blocked with blocking buffer (BB; PBS containing 0.1% Tween-10, 0.2% bovine serum albumin, 1% dimethyl sulfoxide) and 2.9 | Antibodies specificity PCNA, S100β, and GFAP antibodies have been previously documented for their use and their specificity in mouse and in zebrafish according to manufacturer's instruction and/or literature Diotel, Beil, et al, 2015;Dorsemans, Soule, et al, 2017;Marz et al, 2010). Consistent with these previous studies, PCNA-labeling was observed in cell nuclei across the neurogenic niches lining the ventricles.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…19,107,108 Zebrafish is also a common model for investigating a wide variety of physiologic and physiopathological processes including metabolic syndrome and diabetes. [109][110][111][112][113] T2D has been developed by immersing fish in water supplemented with D-glucose, 109,111,114 and T1D has been set up by STZ intraperitoneal (ip) injection. 109 Acute hyperglycemia can be also mimicked by intraperitoneal injection of D-glucose.…”
Section: Partmentioning
confidence: 99%
“…109 Acute hyperglycemia can be also mimicked by intraperitoneal injection of D-glucose. 112 Consequently, zebrafish appear as interesting models for investigating the role of metabolic disorders such as diabetes on the CNS.…”
Section: Partmentioning
confidence: 99%